Impacts of climate change take a toll on Andean potato farmers: participative mapping for the evaluation of potato diversity in the Andes - Shaw, Alison; Kristjanson, Patricia M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Context: Newer farming practices that favour monoculture are dependent on the use of pesticides and chemicals to stave off plagues. Along with human health risks associated with the use of these products, bacteria, virus and pests develop resistance to chemicals and pesticides over time. Also new strains develop periodically. These risks underscore the importance of conserving a diverse pool of potato varieties that may hold natural resistances in their genes. This project is interested in understanding potato biodiversity and what the dynamics of diversity are in higher elevations. More than 10 years of Geographic Information System (GIS) mapping reveals that farmers have ascended the Andes 150 meters during the past 30 years to escape agricultural diseases and pests due to increasing temperatures.